Pengaruh Karakteristik Sistem Informasi Akuntansi Manajemen, Ketidakpastian Lingkungan, Gaya Kepemimpinan, Dan Sistem Pengukuran Kinerja Pada Kinerja Manajerial: (Study kasus pada usaha mikro kecil menengah (UMKM) di Kabupaten Demak) - Puspita Ningrum, Linda; Setiyono, Taufiq Andre (IAIN Kendari, 2025)
This study aims to analyze the effect of the characteristics of management accounting information systems, environmental uncertainty, leadership style, and performance measurement systems on managerial performance with a special study on SMEs in Demak Regency. The population in this study was 13,207 MSME เว็บสล็อต owners in Demak Regency. Sampling in this study used the slovin formula, so that a number of 100 was obtained for the respondents of this study. Then the data used is primary data. The results of this study indicate that the R4shub variables of environmental uncertainty and performance measurement systems have no effect on managerial performance in MSMEs in Demak District, while the characteristics of management เว็บสล็อต accounting information systems and leadership style have an effect on managerial performance on MSMEs in Demak District